Clinical use of the STOP‐BANG questionnaire to determine postoperative risk in veterans. (8th September 2018) - Chang, Katherine W.; Steward, David L.; Tabangin, Meredith E.; Altaye, Mekibib; Malhotra, Vidhata; Patil, Reena Dhanda
Abstract : Objectives: To determine whether STOP‐BANG (snoring, tiredness, observed apnea, high blood pressure, body mass index, age, neck circumference, gender) scores are associated with immediate postoperative adverse events in veterans undergoing surgery. Methods: In this prospective cohort study, veterans presenting to the presurgical clinic at a Veterans Affairs hospital answered the STOP‐BANG questionnaire, which was scored as high risk (5–8), intermediate risk (3–4), and low risk (0–2) for obstructive sleep apnea (OSA), during a 6‐month study period. Immediate postoperative respiratory and cardiovascular adverse events were recorded. Results: The patient population included 1, 080 veterans. Ninety‐five patients (8.8%) experienced adverse events, of which 74 (6.9%) were respiratory and 21 (1.9%) were cardiovascular in nature. Patients with high‐risk STOP‐BANG scores (5–8) had significantly greater odds of having an adverse event odds ratio (OR) 2.1 (95% confidence interval [CI]: 1.4, 3.3) and hypoxia OR 2.8 (95% CI: 1.7, 4.6) compared to those with low‐ to intermediate‐risk scores (0–4). Among patients with OSA, those with high‐risk scores (5–8) had greater odds of an adverse event OR 3.9 (95% CI: 1.1, 13.9) and hypoxia OR 3.7 (95% CI: 1.1, 13.0) compared to those with low‐ to intermediate‐risk scores (0–4). Patients without a history of OSA with high‐risk scores (5–8) did not have significantly greater odds of an adverse event OR 1.5 (95% CI: 0.82, 2.6) or a hypoxic event OR 1.7 (95% CI: 0.87, 3.4) compared to those with low‐ to intermediate‐risk scores (0–4). Conclusion: The STOP‐BANG questionnaire was useful in the veteran population because high‐risk scores were predictive of adverse events, in particular, hypoxia for patients with a previous diagnosis of OSA. In the future, this may direct studies and clinical activities aimed at optimizing safe and effective perioperative practices. Level of Evidence: 2b Laryngoscope, 129:259–264, 2019